Damage Detection of Steel-Concrete Composite Beam = Diagnostyka uszkodzeń stalowo-betonowych belek zespolonych - Szumigała, Maciej; Pełka-Sawenko, Agnieszka; Wróblewski, Tomasz; Abramowicz, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents analysis results of steel-concrete composite beams, identification and attempts to detect damage introduced in a discrete model. Analysis of damage detection was conducted using DDL (Damage, Detection, Localization), our own original algorithm.
Keywords: steel-concrete composite beams; damage; detection; lokalization; Python; ABAQUS; Matlab; belki zespolone stalowo-betonowe; uszkodzenie; detekcja; lokalizacja uszkodzeń